Micro/Macroporous System: MFI‐Type Zeolite Crystals with Embedded Macropores. (23rd December 2014) - Machoke, Albert G.; Beltrán, Ana M.; Inayat, Alexandra; Winter, Benjamin; Weissenberger, Tobias; Kruse, Nadine; Güttel, Robert; Spiecker, Erdmann; Schwieger, Wilhelm
<x xml:space="preserve">Abstract</x> Zeolite crystals with an embedded and interconnected macropore system are prepared by using mesoporous silica particles as a silica source and as a sacrificial macroporogen. These novel hierarchical zeolite crystals are expected to reduce diffusion limitations in all zeolite‐catalyzed reactions, especially in the transformation of larger molecules like in the catalytic cracking of polymers and the conversion of biomass. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>